The development of a complex acoustic deformation method to fix reliable precursors of rock failure under uniaxial compression - Golosov Andrei M. (Федеральное государственное автономное образовательное учреждение высшего образования «Дальневосточный федеральный университет», 2015)
The investigation of the generality of failure of brittle rock samples was carried out in the Laboratory of Geodynamics of the Far Eastern Federal University, Vladivostok, Russia. In the course of testing, the complex acoustic deformation method was used performed by the servocontrol loading machine MTS-816. As a result, established were the regularities of the appearance and development of dissipative mesocracks structures in rock samples under uniaxial compression. The deformation of greatly stressed rock samples was connected with the properties of the acoustic emission radiation of the sample. It enabled one to determine the system of reliable precursors of failure of rock samples both long-term and short-term ones. The system of the precursors represents all stages of the appearance and development of System of reliable precursors of failure involving long-term and middle-term was established. This system of precursors reflects the stages of formation and development of dissipative mesodefect structures in high stressed rock samples.
Keywords: ОБРАЗЕЦ ГОРНОЙ ПОРОД; ROCK SAMPLE; ДЕФОРМИРОВАНИЕ; DEFORMATION; АКУСТИЧЕСКАЯ ЭМИССИЯ; ACOUSTIC EMISSION; PRECURSORS; КОМПЛЕКСНЫХ МЕТОД; COMPLEX METHOD; ПРЕДВЕСТНИКИ РАЗРУШЕНИЯ; 622.02